Rapid Haemodynamic Improvement Following Saruplase in Recent Massive Pulmonary Embolism - Pacouret, Gérard; Barnes, Sarah J.; Hopkins, Gwyn; Charbonnier, Bernard (Thrombosis and Haemostasis, 1998)
In a single centre pilot study, saruplase (20 mg bolus plus 60 mg infusion over 1 h) was administered to twenty patients with an angio-graphically documented recent massive pulmonary embolism: Miller index of at least 20 and mean pulmonary artery pressure of at least 20 mmHg. The lytic ability of saruplase to cause normalization of haemodynamic parameters over the first 12 h and reperfusion of pulmonary arteries at 24 h was assessed. A decrease of 25 ± 10% in total pul monary resistance was evident at 30 min. Haemodynamic parameters continued to improve with total pulmonary resistance decreasing by 29 ± 8% and 40 ± 11% at 1 and 12 h respectively. Relative improve ment in Miller index 24 ± 6 h after saruplase treatment was 38 ± 9%. Two patients suffered recurrent pulmonary embolism, two severe bleeding events were observed. One patient died following a haemorrhagic stroke.